Research on the impact of mixed ownership reform on innovation of state-owned enterprises: Evidence from Chinese industrial enterprises - Xia, Wei; Zhou, Xinmiao (Frontiers in Environmental Science, 2022)
This article focuses the research sample on Chinese State-Owned Enterprises (SOEs), using the Beyond-logarithmic Stochastic Frontier Production Function and the ordinary fixed effect model to examine, and evaluates the influence of mixed ownership reform on the innovation of SOEs from the perspective of incentive and constraint mechanisms. Our study investigates the impact of the corporate governance, policy burden, and environmental regulation. The main conclusions are as follows. First, mixed ownership reform can enhance the innovation capability of SOEs. Second, mixed ownership reform stimulates innovation of SOEs by optimizing corporate governance and reducing policy constraints on enterprises which regulate enterprise decision-making behavior. Third, the environmental regulation also affects SOEs’ innovation. This study can provide a reference for the government to further deepen the reform, optimize the living environment of SOEs, improve environmental regulations and promote the sustainable development of economy.